A High‐Performance Non‐Fullerene Acceptor Compatible with Polymers with Different Bandgaps for Efficient Organic Solar Cells. Issue 5 (6th March 2019) - Liu, Tao; Gao, Wei; Zhang, Guangye; Zhang, Lin; Xin, Jingming; Ma, Wei; Yang, Chuluo; Yan, He; Zhan, Chuanlang; Yao, Jiannian
Abstract : Owing to their good polymer compatibility, fullerene derivatives, such as PC61 BM and PC71 BM, have been the dominant electron acceptors to pair with various polymer donors in polymer solar cells (PSCs). The recent surge of non‐fullerene materials leads to several high‐performance molecular acceptors. Despite their high performance in a given polymer/acceptor system, the generality of these acceptors, i.e., their compatibility with different donor polymers remains uncertain. Here, a high‐performance small molecule acceptor (SMA), BTTIC, is designed and synthesized to combine with three polymers with different bandgaps, namely J71 (1.92 eV), PBDB‐T (1.80 eV), and PTB7‐Th (1.58 eV). Complementary absorption, compatible energy levels, and particularly the favorable morphologies between BTTIC and the three polymers enable high power conversion efficiencies (PCEs), which are 12.8%, 13.2%, and 10.4% for J71:BTTIC‐, PBDB‐T:BTTIC‐, and PTB7‐Th:BTTIC‐based PSCs, respectively, significantly higher than the PCEs of the fullerene‐ or other non‐fullerene‐based counterparts. Moreover, another famous p‐type polymer donor PffBT4T‐2OD, which shows poor solubility in chloroform and has not yet been studied in non‐fullerene PSCs, is also investigated. Processing by dissolving PffBT4T‐2OD and BTTIC in boiling chloroform enables PffBT4T‐2OD:BTTIC‐based PSCs with a PCE of 10.18%, which is significantly higher than that of PSCs (4.78%) before using boiling chloroform processing. The good compatibility of BTTIC with polymers that have either large, moderate, or small bandgaps makes it a promising non‐fullerene acceptor for next‐generation non‐fullerene PSCs. Abstract : A near‐infrared non‐fullerene acceptor BTTIC is well compatible with different bandgap polymers, i.e., J71 (1.92 eV), PBDB‐T (1.80 eV), and PTB7‐Th (1.58 eV), which achieves power conversion efficiencies (PCEs) as high as 12.8%, 13.2%, and 10.4%, with fill factors all over 70%, suggesting BTTIC is a promising non‐fullerene acceptor for polymers selectivity.